Students' difficulty with proportional reasoning in a university quantitative literacy course - Frith, Vera; Lloyd, Pam (South African Journal of Higher Education, 2016)
The ability to reason about changes in quantities expressed in relative terms is essential for a critical awareness of data use in society. We regard this way of thinking, which we term 'proportional comparison', as a threshold concept (Meyer and Land 2003) for academic quantitative literacy. The extent and nature of students' difficulties with learning this concept in a quantitative literacy course for Law students were studied using a phenomenographic type of analysis of students' responses to four test questions, written at different times. Less than a quarter of students could be said to have learned this concept at any time and improvements in students' ability to reason about relative differences were very slight. This supports the view that the learning of "troublesome" (Meyer and Land 2003) quantitative literacy concepts takes a long time and should be addressed in a sustained way, integrated into a student's programme of study.